A model-independent measurement of the expansion and growth rates from BOSS using the FreePower method - Schirra, Adrian P.; Quartin, Miguel; Amendola, Luca (Physics of the Dark Universe, 2025)
In this work we provide a data analysis of the BOSS galaxy clustering data with the recently proposed FreePower method, which adopts as parameters the power spectrum band-powers, the expansion rate, and the growth rate instead of specific cosmological parametrizations. It relies on the Alcock-Paczyński effect and redshift-space distortions, and makes use of one-loop perturbation theory for biased tracers. In this way, we obtain for the first time constraints on the linear growth rate, on the Hubble parameter, as well as on the dimensionless distance H0DA and various bias functions, that are independent of a model for the power spectrum shape and thus of both the early and late-time cosmological modeling. Using weakly-informative priors, requiring basically that σ8∈[0.67,1.07] at 95% CI, we find at zeff=0.38, f=0.67−0.19+0.20, H/H0=1.033−0.081+0.13, H0DA=0.264−0.039+0.026 and at zeff=0.61, f=0.82−0.20+0.25, H/H0=1.085−0.067+0.16, H0DA=0.390−0.046+0.036. We find lower H/H0 results than expected from Planck 2018 ΛCDM results at a confidence level of 1.7σ (2.1σ) for low-z (high-z). These results form a proof-of-principle of the FreePower method. We also get constraints on the bias parameters which are in agreement with constraints from previous BOSS analyses, which serves as a cross-check of our pipeline.
Online verfügbar 28 July 2025, Version des Artikels 1 August 2025
Gesehen am 12.12.2025